KONDISI SOSIAL EKONOMI PENDUDUK KECAMATAN LUBUK KILANGAN KOTA PADANG - Musliadi, Musliadi; Bakaruddin, Bakaruddin; Erita, Yeni (STKIP PGRI Sumbar, 2013)
This study aims to determine the socio-economic conditions of the population in the district of Kilangan Lubuk Padang. This research is descriptive. The population in this study were all families (KK) in District of Lubuk Kilangan totaling 11. 034 households. The samples were taken by using a sample of 100 families with Proportionate random sampling of respondents by sub-sub-populations vary. The research found that: 1) Livelihoods District of Lubuk Kilangan dominant livelihood in agriculture both father and mother to the type of work as agricultural labor, general status as a laborer, a place to do work at home and most do not have a second job, 2) conditions of houses in District of Lubuk Kilangan generally good, where the roof is tile and asbestos, concrete walls, tiled floor of the house, air vents for the entire room, clean source of water taps. Judging from the way of storing food ready for consumption and food consumption of the population is not ready at the general store in a special place and clean, waste water disposal with holes and a general MCK own bathroom and 3) Education of population in the District Lubuk Kilangan generally graduating high school / equivalent, both wife and husband, while the non-formal education is rarely found residents